PERDAGANGAN BERJANGKA SEBAGAI SARANA SISTEM KETAHANAN PANGAN NASIONAL INDONESIA - Samsul, Mohamad (Program Doktor Ilmu Ekonomi, 2010)
The purpose of this research is to optimize the function of futures market to achief the success the National Defence of Food System, The Indonesian government commits that Indonesia to be as an international foodstore. Indonesia has a potensial to be exporter of foods in a globalization era. The negative impact of international free trade can be managed by the futures market to protect the needs of foods of domestic people and industries. The function of National Logistic Body (BULOG) to control the national foodneeds has not been success eventhough already 40 years operation. The Jakarta Futures Market (BBJ) operated since year of 2000 has many weak of functions. BBJ has not been designed in a comprehensive and a well-thought out plan. BBJ was set up careless and so uncapable to develop herself.The system of BBJ has to be totally reorganized. BBJ must operate by national trading system. The Futures Market is obligated to trade all durable product of farm, plantation, forestry, fishery, breeding, mining &gas and financial instruments. In developing Futures Market is abligated too create storing system, transportation system, quality control body and arbitrage body. The development of Futures Market involved many departments such as: Trade, Transportation, farm & Plantation, Mining & Gas, Bulog, Indonesia Commercial Body, Sentral Bank, and regional government.The development of Futures Market is to be planned fairly by National Development Body, because many departments involved.The Futures Market is the latest market after money market and capital market. So, it is to be socialized to politicion, all departments involved, market practation and investors via seminar, short course and formal education. The suscces of National Defence of Food System is very important for Indonesia to face globalization era which will be started at the latest of 2020. Indonesia still has10 years to regulate everything. In the globalization era, no more economic sovereignty of a country. Each country must obey with the regulation of World Trade Organizatation. The Futures Market with unsuccessful operation now will impact to the failure of economic development in the futures.Keywords: Futures market, Natioanl Defence of Foods System, National Trading System.